Probiotics Can Boost the Antitumor Immunity of CD8+T Cells in BALB/c Mice and Patients with Colorectal Carcinoma - Jie Mao; Shu-Ze Zhang; Peng Du; Zhi-Bin Cheng; Huan Hu; Shi-Yao Wang (Journal of Immunology Research)
Background. The drug resistance and the immune suppression in the tumor microenvironment are important factors affecting tumor progression. Reversing drug resistance and changing tumor suppression microenvironment are ideal ways to inhibit tumor progression. Objective. The aim of the study is to verify antitumor immune response of probiotics in patients with colorectal carcinoma and to explore its mechanism. Methods. To detect the tumor samples of 122 patients with colorectal carcinoma after surgery, analyze the effect of probiotics on enhancing tumor-infiltrating CD8+T cells to inhibit colorectal carcinoma, and further verify the mechanism of probiotics on enhancing the antitumor immune response of CD8+T cells through animal experiments. Results. The results of immunohistochemistry showed that the proportion of CD8+T cells in the patients treated with probiotics before surgery was increased significantly than that in other patients (P=0.033). The results of flow cytometry also showed that the proportion of CD8+T cells in the probiotics group was higher than that in the nonprobiotics group (P=0.029). Kaplan-Meier survival estimates also showed that the CD8+T cells, TNM stage, pathology grade, lymphatic metastasis, and probiotic treatment were significantly associated with the progression-free survival (PFS) (χ2=9.684, P=0.002 for CD8+T cells; χ2=5.878, P=0.015 for TNM stage; χ2=7.398, P=0.004 for pathology grade; χ2=8.847, P=0.003 for Lymphatic metastasis; and χ2=4.622, P=0.032 for the group (group A was treated with probiotics before surgery; group B was not treated with probiotics)). The experimental results in mice showed that probiotics could inhibit tumor growth and increase the proportion of CD8+T cells in mice; the difference was statistically significant (P=0.037). It was also found that probiotic feeding could upregulate the expression of T-cell immunoglobulin mucin receptor 1(TIM-1) in CD8+T cells of mice and also found that probiotic feeding could downregulate the expression of programmed cell death protein 1 (PD-1) in CD8+T cells of mice, compared with the nonfeeding group; the difference was statistically significant (P=0.045 for TIM-1 and P=0.02 for PD-1, respectively). In order to further understand the functional status of CD8+T cells, we analyzed interferon-gamma (IFN-γ)+ T cells and tumor necrosis factor-α (TNF-α)+CD8+T cells by flow cytometry. The results showed that the proportion of IFN-γ+ T cells and TNF-α+CD8+T cells significantly increased after probiotic treatment, compared with the nonprobiotic treatment group; the difference was statistically significant (P=0.040 for IFN-γ+ T cells and P=0.014 for TNF-α+CD8+T, respectively). Conclusions. Probiotics can enhance the antitumor immune response of CD8+T cells. It can play a synergistic antitumor role. On the one hand, its mechanism is through regulating intestinal flora, and on the other hand, through regulating the antitumor immune function of CD8+T cells.